2020
DOI: 10.1177/1971400920913763
|View full text |Cite
|
Sign up to set email alerts
|

Nasal cavities and the nasal septum: Anatomical variants and assessment of features with computed tomography

Abstract: The nasal cavities are complex anatomical structures with high inter-individual variability that relates to different functions. Different anatomic variants may manifest at this site, mainly belonging to the nasal septum and turbinates. Precise knowledge of the anatomy and variants is fundamental for both radiologists and ENT surgeons. This article provides an overview of the main anatomic variants and their frequency, according to the existing literature, as well as ongoing research on nasal cavity segmentati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
20
0
6

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 17 publications
(26 citation statements)
references
References 41 publications
(74 reference statements)
0
20
0
6
Order By: Relevance
“…The nasal cavity presents the most cephalic portion of the respiratory system, and the normal functions are to condition air for the respiratory system and facilitate olfaction [ 10 , 11 ]. The most anterior portion of the cavity vestibular region is characterized by a large amount of hair and mucus production, as well as a robust squamous epithelial lining [ 12 , 13 ].…”
Section: Pathways To the Cns And Advantages Of Intranasal Drug Deliverymentioning
confidence: 99%
See 2 more Smart Citations
“…The nasal cavity presents the most cephalic portion of the respiratory system, and the normal functions are to condition air for the respiratory system and facilitate olfaction [ 10 , 11 ]. The most anterior portion of the cavity vestibular region is characterized by a large amount of hair and mucus production, as well as a robust squamous epithelial lining [ 12 , 13 ].…”
Section: Pathways To the Cns And Advantages Of Intranasal Drug Deliverymentioning
confidence: 99%
“…Oxytocin is a reproductive neuropeptide associated with increasing social behavior and memory in animals. When given to healthy humans, intranasal oxytocin has been shown to increase trusting behaviors, e.g., social affiliation, altruism, and empathy [ 11 , 148 , 149 ]. The hope was these findings would benefit patients with autism spectrum disorder (ASD), which is becoming increasingly prevalent and characterized by hallmark deficiencies in these and other behaviors.…”
Section: Clinical Evidence Of Intranasal Delivery To the Brain Therapiesmentioning
confidence: 99%
See 1 more Smart Citation
“…Nasal obstruction caused by NSD induces nasal airflow turbulence that leads to nasal dryness and recurrent sinusitis and turbinate thickening (TH) [ 6 ]. Studies have indicated that an insufficient nasal airway can lead to persistent mouth breathing during the developmental years, causing varying degrees of maxillary constriction [ 7 ]. Mouth breathers show a narrower hard palate than nasal breathers [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…The anatomy of the paranasal region is quite complex and there are great differences between individuals 1 . In particular, variations in the osteomeatal complex may play a role in the pathogenesis of inflammatory diseases of the paranasal sinuses 2 .…”
Section: Introductionmentioning
confidence: 99%